1996
DOI: 10.1007/bf02751534
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal jaundice due to ABO incompatibility in Sri Lankan

Abstract: A prospective study was carried out on 101 neonates with jaundice due to ABO incompatibility. The direct Coomb's test was weakly positive in 4 cases. The indirect Coomb's test using the eluate was positive in 8 cases. In the maternal blood either IgG anti-A or anti-B haemolysin was present in high titre in every case. Phototherapy was given when the indirect serum bilirubin level exceeded 9 mg/dl. Exchange transfusion was done-in 39 cases, 9 babies requiring multiple exchanges. There were 2 deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…15 In contrast, a study from Sri Lanka reported a much higher incidence (75%) of significant hyperbilirubinaemia. 16 Racial differences in ABO HDN associated with a higher incidence of jaundice have been recognized. 17 Racial differences in the frequency and severity of ABO HDN in the South African population and infants in North Carolina, USA have been reported.…”
Section: Discussionmentioning
confidence: 98%
“…15 In contrast, a study from Sri Lanka reported a much higher incidence (75%) of significant hyperbilirubinaemia. 16 Racial differences in ABO HDN associated with a higher incidence of jaundice have been recognized. 17 Racial differences in the frequency and severity of ABO HDN in the South African population and infants in North Carolina, USA have been reported.…”
Section: Discussionmentioning
confidence: 98%
“…As far as we are aware this will be the largest birth cohort study that combines research on the risk factors of NH and follow-up monitoring up to one year of life in South East Asia [912]. The information gathered from this study will be used to improve and adapt existing guidelines for resource-constrained environments, help develop locally relevant protocols, and make evidence-based recommendations on where and how limited resources can be best allocated to reduce the risks and the negative outcomes of NH.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive rates of ET with their attendant risks persist in LMICs (6)(7)(8)(9)(10)(11)(12)(13)(15)(16)(17). The overarching findings from this study are that RET is also highly prevalent and that a risk assessment framework that combines TSB monitoring, ABE status, and the presence of hemolytic disorders is likely to significantly reduce the need for RET.…”
Section: Discussionmentioning
confidence: 63%
“…The high proportion of ABO incompatibility among infants with ET/RET deserves attention based on several reports that found this factor as the most prevalent among infants who received ET and/or RET (9,11,12,28,29). For example, in one study from Iran in which 176 ETs were administered to 150 neonates, ABO incompatibility was the commonest, reported in 49.2% of the infants who had ET and 45% of the 20 infants with RET (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation